Linguistic diversity, school language of instruction policy, and learning outcomes across Asia and the Pacific - Takiko Igarashi; Daniel Suryadarma; Pooja Yadav (Asian Development Bank Institute (ADBI), 2023)
Children appear to learn better when taught in their mother tongue. This finding gives rise to an argument that mother tongue-based multilingual education could effectively improve learning outcomes in low- and middle-income countries. However, the challenges of implementing an effective multilingual education could prove prohibitive in countries with a high language diversity. Before embarking on the process of introducing multilingual education, policymakers should consider whether a correlation between language diversity and learning outcomes exists, and also, whether a particular language of instruction policy, monolingual or multilingual, correlates with learning outcomes. We construct a data set on the language of instruction policy across Asia and the Pacific and combine it with international assessment results. We find no evidence that countries with a richer linguistic diversity, controlling for income level, have significantly different learning levels. We also find evidence that learning outcomes are higher in countries with a monolingual education policy after controlling for income level and language diversity. Our findings imply that policymakers must seriously consider the potential challenges and benefits of a multilingual education policy before implementing it.
Keywords: I21; I28; Z13; 330; linguistic diversity; language of instruction; learning; Asia and the Pacific